Airport Economics in Latin America and the Caribbean : Benchmarking, Regulation, and Pricing - Serebrisky, Tomas (World Bank, 2012)
This report presents the findings of a first-ever, comprehensive study of how Latin America and the Caribbean (LAC) region airports have evolved during a notable period of transition in airport ownership. It is an unbiased, positive analysis of what happened, rather than a normative analysis of what should be done to reform and to attract private sector participation to the airport sector. It takes the first step to respond to the need for more conclusive information about the influence of airport ownership on economic performance. The report centers on the study of three dimensions of performance: productive efficiency, institutional setup for the governance of the sector, and financing. This multifaceted report uses a range of advanced quantitative and qualitative methods to assess the relationship between airport ownership and performance in the LAC region. After a comprehensive overview, chapters 1 and 2 provide the necessary background for the air transport sector and the evolution of private sector participation and investment in airport infrastructure. In chapter 3, questionnaires submitted to airport operators and regulators led to the creation of the unique data sets, which were first used to compare performance across 14 partial performance indicators, and next used to develop aggregate measures of efficiency necessary for the benchmarking exercise. In chapter 4, a qualitative study of the relationship between type of regulating agency (independent or government-led) and transparency, accountability, and bureaucracy provides insight into how recent reforms have also affected the quality of regulatory governance. Chapter 5 provides an in-depth analysis of the evolution of tariff structures in the region as compared to a sample of international airports. Several important topics were not included in this report but should be the focus of future research. In particular, the evolution of the quality of services in airports deserves greater attention, as airports are increasingly becoming business centers and key gateways for trade competitiveness. The other main topic that requires detailed practical research is climate change and its relationship with the airport sector.